Optimization of Culture Conditions on Growth of Chlorella sp. Newly Isolated From Bagansiapiapi Waters Indonesia. Issue 1 (November 2021) - Iriani, D; Hasan, B; Putra, HS; Ghazali, TM
Abstract: Chlorella sp. is a type of micro-sized green algae obtained in fresh or marine waters. However, many factors need to evaluate the growth of Chlorella sp. mainly the culture conditions. This study aimed to evaluate the culture conditions in optimizing the growth of Chlorella sp. newly isolated from Bagansiapiapi marine waters. The experiment was carried out at temperature ±25°C, light intensity 2300 Lux using TL-D lamp (36 W). There were six treatments as culture conditions for the cultivation of Chlorella sp.:1). Bean Sprouts ( Vigna radiata ) Extract Media (BSEM) with light continuously, 2. BSEM with a Photoperiod light:dark (10:14h), 3. Tofu waste media with light continuously, 4. Tofu waste media with a photoperiod light:dark (10: 14h), 5. Fish pellet solutions media (25%), 6. Fish pellet solutions media (50%). The parameter observed was the growth, cell density and the specific growth rate of Chlorella sp. every 2 days for 14 days of cultivation. Based on the results shown that the marine Chlorella sp. from Bagansiapiapi waters could be adapted to all treatments. Nevertheless, the use of BSEM light continuously obtained the highest cell density (27.75 x 10 5 cell/ml) on 12 days and continues to increase until 14 days, while the other treatments had decreased. Furthermore, the Chlorella sp. obtained the specific growth rate was 0.42. Therefore, the marine Chlorella sp. from Bagansiapiapi could be cultivated in BSEM light continuously for further development as a functional food or bioactive source in pharmaceutical products.